Cirurgia para controle do dano: uma revisão - Ricardo Antônio Correia Lima; Patricia Rieken Macêdo Rocco (Revista do Colégio Brasileiro de Cirurgiões)
Damage control surgery is one of the major advances in surgical practice in the last 20 years. The indications for damage control surgery are: the need to terminate a laparotomy rapidly in an exsanguinating, hypothermic patient who had developed a coagulopathy and who is about to die on the operating table; inability to control bleeding by direct hemostasis; and inability to close the abdomen without tension because of massive visceral edema and a tense abdominal wall. Damage control surgery has three phases: 1) laparotomy to control hemorrhage by packing, shunting, or balloon tamponade, or both; control of intestinal spillage by resection or ligation of damaged bowel, or both; 2) physiological resuscitation to correct hypothermia, metabolic acidosis, and coagulopathy. 3) planned reoperation for definitive repair. Damage control surgery is appropriate in a small number of critically ill patients who are likely to require substantial hospital resources. However, there are many questions that need to be answered. Who is the patient elected for this surgery? When is the ideal time to make the decision? Which are the parameters that indicate to the surgeons the moment to re-operate the patient? How to treat the long-term complications? In the present review we described some historical aspects, indications, technical aspects, advantages and disadvantages of this procedure, as well as its physiological consequences and morbidity and mortality rates of damage control surgery. Damage control surgery offers a simple effective alternative to the traditional surgical management of complex or multiple injuries in critically injured patients.